Changes of Poleward Oceanic Heat and Salt Transport Associated With the Central Eurasian Seaway During the Early Paleogene - Chenguang Zhu; Jian Zhang; Chenyu Zhu; Congcong Gai; Chengshan Wang (Geophysical Research Letters, 2025)
Abstract During the early Paleogene, the Arctic Ocean existed in a warm yet restricted freshwater regime, with episodic strong freshening leading to proliferation of the freshwater‐adapted Azolla at basal middle Eocene times (49–48 Ma). The Kara Strait, located between the Arctic Ocean and the West Siberian Sea (WSS), facilitated an open central Eurasian seaway before the middle Eocene and the temporal coincidence of the strait's initial closure with the Azolla expansion suggests a causal link. Here with numerical modeling, we demonstrate that the open central Eurasian seaway constitutes a conveyor for heat and salt transport from subtropical to high‐latitude waters, accompanied by wind‐induced northward currents through the WSS. The closure of the Kara Strait disrupts this poleward transport, leading to cooling and freshening of both the Arctic Ocean and the WSS. The resultant decline in Arctic surface salinities might have favored the Azolla Event.